2001
DOI: 10.1089/088922201750236942
|View full text |Cite
|
Sign up to set email alerts
|

Trial-Related Discrimination in HIV Vaccine Clinical Trials

Abstract: Participants in preventive HIV vaccine trials may experience negative social consequences of trial participation, including problems related to a vaccine-induced positive HIV antibody test, yet few vaccine studies have reported on this issue. From October 1995 through November 1998, 1516 AIDS Vaccine Evaluation Group (AVEG) volunteers were assessed for reports of trial-related discrimination (TRD). Ninety TRD events were reported by 76 (5%) of 1516 volunteers. The most commonly reported incidents (n = 52, 57.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 12 publications
2
43
1
1
Order By: Relevance
“…16,27,32,33 In several studies, discrimination ranged from < 5% to 30%. [34][35][36][37][38][39][40] Only about 4% of participants reported PIEs in this study, a finding that was similar to another trial in Thailand. 40 This could be due to differences in the background and culture of the study community as well as different procedures in assessing PIEs among participants.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…16,27,32,33 In several studies, discrimination ranged from < 5% to 30%. [34][35][36][37][38][39][40] Only about 4% of participants reported PIEs in this study, a finding that was similar to another trial in Thailand. 40 This could be due to differences in the background and culture of the study community as well as different procedures in assessing PIEs among participants.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to other studies, the most frequent PIE reported in this study was personal relationship problems, especially for women. 35,37 In addition, female student participants experienced stigma during the first 6 months after enrollment. This could be due to lack of knowledge and misunderstanding about HIV/AIDS at the early phase of the trial, as PIEs were much less frequent after that period.…”
Section: Discussionmentioning
confidence: 99%
“…HIV vaccine recipients may experience stigmatization or discrimination in situations where an HIV test is determining important decisions, such as donating blood, obtaining a life or health insurance, or for purposes of immigration or employment. 4,22,23 In Belgium, the PRISM HIV O Plus test is used for the centralized screening of blood donors, in combination with HIV nucleic acid testing (NAT) of pooled samples. A positive screening test result, as observed in 48% of subjects in this study, will automatically lead to exclusion from blood donation, irrespective of NAT and confirmation test results.…”
Section: Discussionmentioning
confidence: 99%
“…Provide clear and accurate descriptions of the study design (Mills et al, 2004). Be prepared to address the volunteers' concerns, especially regarding safety and trial-related discrimination (Allen et al, 2001). Take an active role in the community by giving presentations about the research, providing educational information on how vaccines protect, and by discussing ways individuals can reduce risk factors for HIV (Ravanfar et al, 2009).…”
Section: Clinical Recommendationsmentioning
confidence: 99%